The Influencer Economy and the Multiplier Effect on the Value Chain of Local Products - Farkhatun Zaidah (PT. Anagata Sembagi Education, 2025)
This research analyzes the impact of the influencer economy on the multiplier effect in the value chain of local products through a quantitative approach. Digital transformation and the role of digital influencers have transformed the dynamics of local product marketing, creating significant multiplier effects on regional economies. Using quantitative analysis methods, this study measures the magnitude of multiplier effects on various aspects of the local product value chain, including income, employment, and added value. The research results show that the influencer economy generates output multipliers of 1.4-1.6 for local products, with the most significant effects in the food sector and quality products with quality labels. Digitalization through short marketing channels and e-commerce platforms has been proven to strengthen local multiplier effects with LM3 values > 2. This research contributes to theoretical understanding of multiplier effect mechanisms in the digital era and provides practical implications for regional economic development through optimizing the role of digital influencers in local product marketing.